2022
DOI: 10.15376/biores.17.3.4086-4097
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tree age, thickness, and depth of timber on density and mechanical properties of heat-treated black poplar wood (Populus nigra)

Abstract: ThermoWood is a wood modification method that is used to improve the wood application and dimensional stability of wood. In this study, poplar wood (Populus nigra) was used in two age groups of 18- and 38-year-old trees to investigate the effect of tree age, thickness, and depth of heat-treated timbers on mechanical properties and density. In each age group, the timbers were prepared according to thickness of 40, 50, and 60 mm. The experimental samples were prepared from the surface (S) and middle (M) depth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This difference is caused by the increased density of older trees (Bijak and Lachowicz 2021). Hassani et al (2022) found that the mechanical properties of Populus nigra increased when the age of tree increased. They related it with the fiber length and cell wall thickness, which affect the increasing of density of the wood.…”
Section: Physical and Mechanical Propertiesmentioning
confidence: 99%
“…This difference is caused by the increased density of older trees (Bijak and Lachowicz 2021). Hassani et al (2022) found that the mechanical properties of Populus nigra increased when the age of tree increased. They related it with the fiber length and cell wall thickness, which affect the increasing of density of the wood.…”
Section: Physical and Mechanical Propertiesmentioning
confidence: 99%